Integrated Reporting Elements Analysis of Mining and Manufacture Companies in Indonesia - Gita Astyka Rahmanda; Zuhrotun; Indah Kartika Sandhi (Kusuma Negara Business School, 2020)
This research aims to analyze the implementation of integrated reporting elements by mining and manufacture companies in Indonesia. The analysis consists of scoring the number of the Integrated Reporting (IR) element conducted by mining and manufacture companies listed on the Indonesia Stock Exchange. Research data was taken from Companies’ Annual Report, sustainability report and other information published on IDX. This research analyzes the main eight indicator of Integrated Reporting. A purposive sampling method is used in this research to determine the research sample. Analytical technique used in this research is descriptive statistical analysis. Research finding shows that 68.3% of companies have implemented eight IR elements. Among those companies, only ten companies enumerated in Integrated Sustainability Reporting Award. The transformation report policy suggested by OJK in integrating Sustainability Reporting, Corporate Social Responsibility and Annual Report into an Integrated Report motivates manufacture and mining companies to present their performance information corresponding to International Integrated Reporting Framework